Butenko during his interview at Rome on 18 February. Prove of his being the real Soviet Ambassador who disappeared from Bucharest, dated 25 February
Butenko during his interview at Rome on 18 February. Prove of his being the real Soviet Ambassador who disappeared from Bucharest, dated 25 February.